Patterns of foliar δ15N and their control in Eastern Asian forests. Issue 5 (10th March 2012) - Fang, Yunting; Koba, Keisuke; Yoh, Muneoki; Makabe, Akiko; Liu, Xueyan
Abstract: Foliar δ 15 N has been used increasingly in research on ecosystem nitrogen (N) cycling, because it can serve as an integrator of ecosystem N cycling and thus has a potential to reveal temporal and spatial patterns of N cycling as well as how the N cycle is altered by disturbances. However, the current understanding on controls of foliar δ 15 N is based principally on studies from America, Europe, Australia and Africa. Here we compiled data from 65 forests at 33 sites across East Asia to explore regional patterns and what controls foliar δ 15 N by linking it to climate, species composition, soil depth, slope position, N deposition, and soil N availability. In East Asia, foliar δ 15 N ranged from −7.1 to +2.7‰. Mean foliar δ 15 N values for tropical, subtropical and temperate forests were all −3.1‰, which was unexpected. The patterns of foliar δ 15 N with precipitation, temperature and altitude were not clear. The variation in foliar δ 15 N among species and between different slope positions appeared to be small within a given forest. The δ 15 N for both bulk soil N and extractable inorganic N generally increased with soil depth as expected, strengthening the idea that deep‐rooted trees may have access to 15 N‐enriched N. Different from the positive correlations reported across America and Europe, in East Asia we found that foliar δ 15 N decreased with increasing N deposition and did not relate to soil N availability. These discrepancies deserve more research to elucidate the mechanisms by which foliar δ 15 N is affected by ecosystem N availability at a regional scale.